Model Driven PID Controller in Water Heater System - Tommy Hondianto; Erwin Susanto; Agung Surya Wibowo (Institute of Advanced Engineering and Science, 2016)
PID controller has been widely used as one of the basic property controllers in industry. However, tuning PID parameters is not simple and also has a few problems in handling slow response systems, such as boiler. Therefore, the Model Driven PID (MD PID) control is designed for solving these problems, especially for plants or processes with slow response. The MD PID is using the model of the plant itself as the basic model of the controller. In this research, we will show the performance of water heater system step response with MD PID controller compared to the conventional PID controller (PI controller). The MD PID closed-loop system is expected to give fast response, stable, and no overshoot.